A Sociological Assessment of The Impact of Approaches to Premature Children on Parents - Toprak, Murat (Fırat University, 2025)
This study, which deals with human relationships that emerge with experience, emphasizes the changing social reality of people in the process. Having a premature child with special needs has significantly affected the social relations of parents. With this impact, the parents entered into an intense and fast-paced process and experienced a significant change in their lives, either consciously or unconsciously. Parents, who first experienced the change in their own inner world and private sphere, started to experience transformation in their relationships in the public sphere with the addition of socialization. In this context, the study aims to examine the changing social relations and everyday lives of parents with a premature child with special needs. It also examined how parents meet the needs of their child while experiencing their everyday lives. Qualitative research method was used in the study and in-depth interviews were conducted using semi-structured questionnaire technique. The study draws attention to the fact that with the change, there are both intensity and individual differences in the social relations that parents establish with the outside world. Parents who experienced stigmatization intensely in their approaches towards their children were found to avoid, react to or ignore events, people and places that negatively affected their children's development.

Deneyimle beraber ortaya çıkan insan ilişkilerini ele alan bu çalışma, insanların süreç içerisinde değişen sosyal gerçekliği üzerinde durmuştur. Özel gereksinimli prematüre çocuğa sahip olmak ebeveynlerin sosyal ilişkilerini önemli ölçüde etkilemiştir. Bu etkilenmeyle beraber ebeveynler yoğun ve tempolu bir sürecin içine girerek farkında olarak ya da olmayarak belirgin bir şekilde yaşamlarında bir değişim yaşamıştır. Değişimi ilk olarak kendi iç dünyası ve özel alanında yaşayan ebeveynler, sosyalleşmenin de eklemlenmesiyle kamusal alandaki ilişkilerde de dönüşüm yaşamaya başlamıştır. Bu bağlamda çalışma, özel gereksinimli prematüre çocukla beraber ebeveynlerin değişen sosyal ilişkilerini ve gündelik hayatlarını irdelemeyi amaçlamıştır. Ayrıca ebeveynlerin gündelik hayatlarını deneyimlerken çocuğunun ihtiyaçlarını nasıl karşıladığı incelenmiştir. Çalışmada nitel araştırma yöntemi kullanılmış ve yarı yapılandırılmış soru tekniğiyle derinlemesine görüşmeler gerçekleştirilmiştir. Çalışma, değişimle beraber ebeveynlerin dışarıya yönelik kurduğu sosyal ilişkilerde hem yoğunluk hem de bireysel açıdan farklılıklar olduğuna dikkat çekmiştir. Çocuklarına karşı yaklaşımlarda damgalanmayı yoğun olarak yaşayan ebeveynler, onların gelişimine olumsuz etkileyen olay, kişi ve mekânlardan uzak durduğu, tepki verdiği ya da görmezden geldiği saptanmıştır.
Prematüre Çocuklara Yaklaşımların Ebeveynler Üzerindeki Etkisine Yönelik Sosyolojik Bir Analiz
Keywords: Sociology of Family and Relationships; Aile ve İlişkiler Sosyolojisi; Sociology of Health; Sağlık Sosyolojisi; Social Change; Sosyal Değişim; Sociology of Child; Çocuk Sosyolojisi